Perlindungan Hukum Terhadap Nasabah atas Kejahatan Phising dan Hacking pada Layanan Bank Digital Ditinjau Berdasarkan Hukum Positif Indonesia - Salsabila Chairunnisa; Tarsisius Murwadji; Nun Harrieti (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Phishing and hacking crimes are cybercrimes that often occur in banking. Therefore, the purpose of this research is to examine the responsibility of digital banks and legal protection for phishing and hacking crimes of customers in digital bank services. Researchers have concluded that the responsibility of digital banks for phishing and hacking crimes to customers in using digital banks service is reviewed based on Indonesia’s Positive Law. Digital banks are responsible in this case for confirming phishing and hacking crimes, making customer complaint handling services accessible to customers in 24 hours. Banks compensate for losses suffered by customers to always maintain the principle of customer trust in them. However, if the customer is unsatisfied with the internal settlement with the digital bank, then the customer is not followed up by the bank concerned. The customer’s legal protection for phishing and hacking crimes is reviewed based on Indonesian Positive Law. The government as a regulator provides legal protection to customers in order to achieve order and legal certainty.